Evaluation of local carotid stiffness and inflammatory biomarkers in stable angina pectoris - Aslan, Abdullah Nabi; Özcan, Ayşe Nur; Ayhan, Hüseyin; Sivri, Serkan; Çelebi, Filiz; Ercan, Karabekir; Durmaz, Tahir (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction: Arterial stiffness (AS) is a well-accepted and reliable predictor of atherosclerotic diseases. Inflammation plays an important role in the development of AS. Aim : To evaluate local carotid stiffness (CS) together with fibrinogen and high-sensitivity C-reactive protein (hsCRP) levels in stable angina pectoris (SAP) patients. Material and methods : The study consisted of 353 consecutive patients with SAP. All underwent coronary angiography (CAG) after the evaluation of local CS parameters and carotid intima-media thickness (IMT) from both common carotid arteries by a real-time echo-tracking system. Baseline inflammatory biomarkers, serum hsCRP and fibrinogen levels were measured. Based on CAG findings, the patients were classified into 4 groups: control subjects with normal coronary arteries (group 1, n = 86), single-vessel disease (group 2, n = 104), double-vessel disease (group 3, n = 95) and triple-vessel disease (group 4, n = 68). Results : The mean carotid pulse wave velocity (PWV) in patients with angiographically confirmed coronary artery disease (CAD) was significantly higher than that in patients with normal coronary arteries (7.82 ±1.76 vs. 6.51 ±0.85 cm/s, p = 0.001). The mean carotid IMT was detected to be significantly higher in group 4 patients compared to those in group 1 (p < 0.001) and group 2 (p = 0.001). Significant correlations were observed between both inflammatory biomarkers and the number of diseased vessels and carotid PWV. Using multi-variate analysis, carotid stiffness, carotid IMT, hsCRP and fibrinogen were independently associated with the presence and extent of CAD. Conclusions : Local CS, carotid IMT, hsCRP and fibrinogen levels are significant predictors of atherosclerotic burden and they may facilitate the identification of high-risk patients for the early diagnosis and prompt treatment of CAD.